Magnetic, structural and surface properties of functionalized maghemite nanoparticles for copper and lead adsorption - Guivar, JAR (2017)
In this study, magnetic nanocomposites were developed and used as adsorbents for lead and copper from aqueous media. Structural, surface, magnetic and textural properties of functionalized maghemite nanoparticles synthesized by alkaline co-precipitation were studied. The surfaces of the iron oxide nanoparticles (Nps) were modified with different chemical agents such as fatty and amino acids, silica (SiO2), mesoporous silica (SBA-15), hydroxyapatite, multiwall carbon nanotubes (MWCNTs) and ethylenediaminetetraacetic acid (EDTA), obtaining NPs with mean particle sizes ranging from 7 to 16 nm according to Rietveld refinement and TEM images analysis. The physicochemical surface properties of the functionalized materials were studied via zeta potential (z) and Fourier transform infrared (FTIR) spectroscopy. Mossbauer spectroscopy (MS) as a function of temperature and DC magnetometry were ¨ used to study the magnetic properties. The superparamagnetic relaxation was studied by MS. The resolved spectra at 20 K confirm the presence of nanomaghemite phase. Besides, the saturation magnetization varies from 12 to 62 emu g 1 . A nitrogen adsorption–desorption technique was used to determine the specific surface area and to study the porous structure. The functionalized g-Fe2O3 Nps exhibited a Brunauer–Emmett–Teller (BET) specific surface area ranging from 74 to 214 m2 g 1 and revealed remarkable uptake capacities to remove Cu(II) and Pb(II) species from aqueous solutions